Estudo do self estendido e a relação com os paradoxos tecnológicos na posse de smartphones - Martins, Valquíria Marchezan Colatto (2018)
Through the study of Belk (1988), about the extended self, it is noted that consumers can find in their possessions an extension of your identity. The focus of this research was the possession of smartphone. The overall goal was to identify whether there is a relationship between self extended and the presence of paradoxes of technology in possession of smartphones in users of Rio Grande do Sul. As to the method, the research is classified as applied, quantitative and descriptive and field (survey). The research subjects were 400 users of smartphones, located in Porto Alegre, Santa Maria and pellets. To measure the self extended scale was used to Sivadas and Machleit (1994), and the scale of Schifferstein and Zwartkruis-Pelgrim (2008). For the paradoxes of technology, we used scale developed by Gonçalves (2012). Using the software SPSS 20.0®, we elaborated lifting the profile of the sample and descriptive statistics. To identify the presence of paradoxes, was performed test of Mann-Whitney non-parametric test. In the analysis of the comparison of means between the sociodemographic variables, we used ANOVA test and significance, Kruskal-Wallis test for income and marital status, and Mann-Whitney test for sex. It was carried out Pearson's Correlation to identify associations between the variables and linear regression to investigate the existence of the relationship. The results for the overall sample (400), the average end of the extended self construct was 2.59, it is not possible to affirm that the smartphone is used as an extension of the identity of those users. The paradoxes of technology identified in the general sample, with weak intensity Freedom/Slavery, with average intensity engagement/disengagement, and with strong intensity the paradoxes Efficiency/inefficiency, Satisfaction/Creation of need, Independence/dependence, Public/Private and Autonomy/addiction. It was identified 56 interviewed that they had presented self extended in the ownership of smartphones. These had obtained equal average or better than 3,6 for construto. The sociodemographic profile of these shows that 71.4% are women and only 28.6% are men. The paradoxes identified in this group with weak intensity Planning/Improvisation and with strong intensity the paradoxes Freedom/enslavement, Satisfaction/Creation of need, Integration/Isolation, Independence/dependence and engagement/disengagement. The Pearson correlation showed that only the variables of satisfaction, Chaos, public and obsolete showed significant correlation with the variables of self extended. In the linear regression, the paradox of Control/Chaos (0.337) showed a higher value, but no paradox presented a value close to 1, it is not possible to affirm the existence of a relationship with self extended. Through this study, we managed to analyze the behavior and user profile of the smartphone technology. In the sample that presented extended self, the majority are women, and moreover, showed higher averages for the variables of the paradoxes of technology than the sample that was not extended self. Even so, the linear regression showed the non-existence of a relationship between the constructs analyzed.